PERENCANAAN STRATEGIS PEMBANGUNAN DESA DI DESA PINGIT KECAMATAN RAKIT KABUPATEN BANJARNEGARA - Dwi Okta Nugroho; Dyah Hariani; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Implementation of the Rural Development Plan implemented through Empowerment, Participatory, in favor of the public, open, accountable, selective, efficient, accurate, sustainability, and through an iterative process in order to obtain effective results. Here is an opportunity for the implementation of bottom-up planning by promoting community participation (participatory society). Further Regulation of the Minister of Home Affairs Number 66 Year 2007 concerning Rural Development Planning, chapter 2 (paragraph 3) states that RPJMDes village contains financial policy, rural development strategy and work program villages. The purpose of research is to describe the development planning in Pingit village, District Rakit, Banjarnegara, describe and analyze the development strategy in Pingit village, District Rakit, Banjarnegara. Efforts to address the problem and the purpose of the research carried out by using the theory of strategic planning by using the SWOT analysis and the Litmus Test as a way to address concerns and goals of research conducted in the strategic planning of the construction village, in the village of Pingit, Subdistrict Rakit, Banjarnegara. The results showed that the development in the Village Planning Pingit starting from the lowest level of the RT level, which is then submitted at the time of execution Musrenbangdes.So it can be said Pingit village development planning using the planning system bootom up planning. This approach is an effort to involve all stakeholders from the beginning, so that any decision is taken in planning their decision together, and encourage the involvement and commitment to fully implement them.